Handbook of Academic Integrity 2015
DOI: 10.1007/978-981-287-079-7_4-1
|View full text |Cite
|
Sign up to set email alerts
|

Academic Integrity Campaign in Indonesia

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
0
10
0
2
Order By: Relevance
“…Students are brought to a certain value that prohibits academic cheating. Strong culture expected to prevent and overcome academic dishonesty (Siaputra and Santosa 2016). This study expects that the relationship academic integrity culture and intention will remain negative under Indonesia environment.…”
Section: Academic Integrity Culture and Intention To Conduct Academicmentioning
confidence: 95%
“…Students are brought to a certain value that prohibits academic cheating. Strong culture expected to prevent and overcome academic dishonesty (Siaputra and Santosa 2016). This study expects that the relationship academic integrity culture and intention will remain negative under Indonesia environment.…”
Section: Academic Integrity Culture and Intention To Conduct Academicmentioning
confidence: 95%
“…In response to this and subsequent national policy, Indonesian educational institutions have made efforts to address the plagiarism issue through prevention and mitigation (as reported in Adiningrum 2015;Adiningrum et al 2013;Siaputra 2013, Siaputra andSantosa 2015). Strategies introduced include workshops and dissemination of plagiarism information, statements on webpages, mandatory uploading of academic work to a database for Indonesian academic staff and students called Garba Rujukan Digital (Garuda) (Dikti 2011a) and validation of academic work through peer review by a specialised team in each institution before promotion of academic staff (Dikti 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The modes of corruption that occur in university institutions include extra tuition fees for graduate student's courses, additional fees for activities of institutional visits, delay or absence of lecturers in lecture hours, extortion from faculty to students, the payment of administrative fees for borrowing books, and the maintenance of course grade and diplomas being legalized. Siaputra et al, (2015) examined the academic integrity of universities in Indonesia explicitly. Siaputra et al, (2015) found that the governance of a university was still marred by acts of academic violations committed by lecturers, invigilators, staff employees, and students.…”
Section: Corruption Practices In University Governancementioning
confidence: 99%
“…Siaputra et al, (2015) examined the academic integrity of universities in Indonesia explicitly. Siaputra et al, (2015) found that the governance of a university was still marred by acts of academic violations committed by lecturers, invigilators, staff employees, and students.…”
Section: Corruption Practices In University Governancementioning
confidence: 99%
See 1 more Smart Citation